Impact of a 4-Week Intensified Endurance Training Intervention on Markers of Relative Energy Deficiency in Sport (RED-S) and Performance Among Well-Trained Male Cyclists - Stenqvist, Thomas Birkedal; Torstveit, Monica Klungland; Faber, Jens; Melin, Anna Katarina (Frontiers in Endocrinology, 2020)
Cyclists often apply block periodization to high training volumes in meso- and macrocycles to optimize training adaptation and to prepare for competition. Body mass influences performance in many sports, including endurance disciplines, and conditions related to the syndrome Relative Energy Deficiency in Sports (RED-S) such as metabolic adaptations and premature osteoporosis have also been reported in male cyclists. This study aimed to determine how a four-week mesocycle of intensified endurance training designed to increase performance, would affect markers of RED-S in well-trained male cyclists. Twenty-two participants (age: 33.5 ± 6.6 years, height: 181.4 ± 5.2 cm, weight: 76.5 ± 7.4 kg, peak oxygen uptake (V̇O2peak): 63.5 ± 6.6 mL·kg-1·min-1) were recruited and instructed to maintain their background training load and to follow a supervised training protocol consisting of three high-intensity interval training sessions/week with a work duration of 32 minutes/session. Protocols included pre- and postintervention assessment of resting metabolic rate (RMR), body composition and bone health by dual-energy X-ray absorptiometry (DXA), blood samples, energy intake, and aerobic performance. The training increased participants’ aerobic performance - peak power output [4.8%, p < 0.001], V̇O2peak [2.4%, p = 0.005], and functional threshold power [6.5%, p < 0.001] as well as total testosterone levels [8.1%, p = 0.011] - while no changes were observed in free testosterone [4.1%, p = 0.326]. Bodyweight, body composition, and energy intake were unchanged from pre- to posttest. Triiodothyronine (T3) [4.8%, p = 0.008], absolute RMR [3.0%, p = 0.010], relative RMR [2.6%, p = 0.013] and RMRratio [3.3%, p = 0.011] decreased, and cortisol levels increased [12.9%, p = 0.021], while no change were observed in the total testosterone:cortisol ratio [1.6%, p = 0.789] or free testosterone:cortisol (fT:cor) ratio [3.2%, p = 0.556]. In conclusion, four weeks of intensified endurance interval training increased the athletes’ aerobic performance and testosterone levels. However, negative changes in markers related to RED-S; reduction in RMR and T3, and an increase in cortisol were observed. These results indicate the complexity involved, and that male athletes are at risk of developing clinical indications of RED-S even during a short four-week endurance training mesocycle.